Attitudes of heterosexual assisted living residents toward gay and lesbian peers - Donaldson, Weston, author; Vacha-Haase, Tammi, advisor; Banning, James, committee member; Lehmiller, Justin, committee member (Colorado State University. Libraries, 2012)
Sexual minorities in post-retirement care facilities fear discrimination and suboptimal care due to homophobia and heteronormative policies. This qualitative study explored the attitudes of 13 heterosexual assisted facility residents toward gay and lesbian peers in their facility. Although most participants reported that they were comfortable talking about homosexuality, the feelings, beliefs, and behaviors toward gay and lesbian residents that they described ranged from favorable, to ambivalent, to unfavorable. Results seemed to indicate that heterosexual residents still view sexual minorities as "others" who are unlikely to inhabit the same spaces they do. Recommendations for further research are provided in order to ameliorate the conditions of aged care facilities for all residents, including sexual minorities.
Keywords: gay and lesbian; assisted living; heterosexual; qualitative; resident attitudes